An overview of moisture damage in asphalt mixtures - Hamzah, Meor Othman; Kakar, Muhammad Rafiq; Hainin, Mohd Rosli (Penerbit UTM Press, 2016)
This paper presents a short review on moisture induced damage in asphalt mixtures. Moisture induced damage is one of the most common causes of pavement distress that results in loss of strength, stripping, raveling, fatigue damage and permanent deformation. Different mechanisms have been used to explain the process of moisture damage in asphalt pavements. However, the moisture damage mechanism takes place due to the interaction of several different processes. The applicability of a single test method to evaluate moisture damage is impractical to a wide range of materials and conditions. Therefore, a new laboratory based testing procedure and analysis protocol is required, with the aim to simultaneously consider the effects of both traffic impact and moisture damage. The proper material design, efficient construction methods, reliable laboratory techniques and well planned highway surface and subsurface drainage systems may lead towards a sustainable asphalt pavement that is sufficiently durable to resist moisture damage. Although considerable advances concerning the subject have been reported, yet there is still a need to address certain issues that are actually involved in the process of asphalt mixture moisture susceptibility.